Non-pollinating fig wasps associated with Ficus andicola (Moraceae) in the Central Andes of Colombia - CARDONA, WILLIAM; CHACÓN DE ULLOA, PATRICIA; KATTAN, GUSTAVO (Revista Colombiana de Entomología, 2007)
Several species of wasps may develop inside the inflorescences (figs) of Ficus spp. These species include the pollinator, usually a single species, while the other species do not provide any benefits to the tree; instead, they may affect negatively the number of seeds and pollinators produced. In this work we studied the composition of the nonpollinating fig wasp fauna associated with Ficus andicola in the Central Cordillera of the Colombian Andes. We examined 418 figs that were collected from 12 trees; the wasps that emerged from each one were counted and separated into morphospecies. A total of 46.5% of flowers produced seeds and 53.5% produced wasps. Twenty-two morphospecies were found emerging from figs of F. andicola. The eight most abundant were identified to genus. The most abundant morphospecies, which were present in more than 40% of figs, were Idarnes sp1, Heterandrium sp. and Idarnes sp2. Most wasp species were found in less than 10% of figs. Based on species accumulation curves, the 22 morphospecies found represent 88% of the expected number of species for F. andicola.